Analysis of Ground Ozone and Its Correlation with Meteorological Parameters over Kigali, Rwanda - Ndayisenga, J. D. (New Visions in Science and Technology Vol. 5, 2021)
The ground ozone concentration over Kigali is directly proportional to solar radiation, especially when the air temperature is less than or equal to 19oC, but when the air temperature exceeds this range, the ozone concentration begins to decrease, but R2 is very low, implying that there is a very low probability of this happening. The ambient ozone concentration is inversely related to solar radiation for wind speeds between 2 and 2.81 m/s, while ambient ozone increases as solar radiation increases for wind speeds above 2.81 m/s. When the wind speed is between 2 and 2.81 m/s, the ambient ozone concentration rises as atmospheric relative humidity rises, but when the wind speed is greater than 2.81 m/s, the ambient ozone concentration falls as atmospheric relative humidity rises. With a calm state of 0%, the average wind speed observed was 3.7402 m/s. The predominant wind direction was west-south with a frequency of 31%, followed by southeast and southwest with a frequency of 22 percent with maximum wind speeds of 6–7.62 m/s. Therefore, if there is a pollutant source in west, southwest, southeast, south or east area, it might be dominantly dispersed in north, northwest, northeast area during July to September 2020. Wind speed measured at lower lever of 10.3ppb to 20.2ppb was 4.3217 m/s with westerly, Westsouth, southeast dominant direction with frequency of about 18%, 30%.For values larger than 20.2 ppb, ambient ozone was carried from a variety of directions, including west, southwest, south, southeast, and east, with maximum wind speeds ranging from 6 to 7.62 m/s.